Multidisciplinary Evaluation and Management of Cavernous Sinus Thrombosis: Integrating Laboratory Diagnostics, Advanced Imaging, Epidemiologic Insights, and Primary Care Approaches - Asiri, Amani Khamash Hassan; Murdi Ali Naser Aldawsari; Abdurhman Majed Ali Aldawsari; Bader Fayz Mohammed Aldawsari; Misfer Marzooq Mohammed Aldawsari; Turki Mohammed Sultan Hakami; Abrar Sayer Almutairi; Maha Sameer Alanazi; Hani Ghazi Abdulmalik; Mohammed Abdulrahman Babaseel; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Cavernous sinus thrombosis (CST) is a rare but lifethreatening neurovascular condition arising from infectious or aseptic etiologies. Its proximity to critical cranial nerves and the internal carotid artery contributes to rapid neurological and ophthalmologic deterioration when diagnosis and treatment are delayed. Aim: This study aims to synthesize multidisciplinary perspectives on CST—integrating epidemiology, risk factors, clinical features, diagnostic strategies, and management approaches—to support early identification and improve patient outcomes. Methods: A comprehensive review of CSTrelated anatomy, pathophysiology, clinical presentation, imaging modalities, laboratory evaluation, and current therapeutic practices was conducted. Emphasis was placed on evidencebased antimicrobial therapy, anticoagulation strategies, surgical indications, and interprofessional care models. Results: CST occurs most frequently secondary to facial, sinus, or orbital infections, with Staphylococcus aureus being the most common pathogen. Key clinical features include fever, headache, periorbital edema, ophthalmoplegia, and cranial nerve palsies, with bilateral involvement often developing as thrombosis propagates. Contrastenhanced CT/MRI with venography provides the most reliable diagnostic confirmation. Early initiation of broadspectrum intravenous antibiotics, combined with anticoagulation when appropriate, significantly reduces mortality from historical levels exceeding 80% to approximately 10–30% today. Multidisciplinary management remains essential due to the high risk of visual loss and persistent cranial neuropathies. Conclusion: Timely, coordinated, and evidencebased intervention markedly improves survival and functional outcomes in CST. Despite advancements, morbidity remains significant, reinforcing the need for early recognition, prompt imaging, and integrated care strategies.